2019
DOI: 10.1016/j.joei.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of catalyst bed temperature and properties of zeolite catalysts on pyrolysis-catalysis of a simulated mixed plastics sample for the production of upgraded fuels and chemicals

Abstract: This is a repository copy of Influence of catalyst bed temperature and properties of zeolite catalysts on pyrolysis-catalysis of a simulated mixed plastics sample for the production of upgraded fuels and chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(56 citation statements)
references
References 26 publications
2
54
0
Order By: Relevance
“…[40] This configuration also allows for more facile recovery of spent catalysts for regeneration. [109] Fluidized-bed reactors (FBR) have better overall potential for scale-up than single-stage fixed-bed reactors because they can overcome operational problems such as heat transfer. [13,22,27,40,46,51,153,[250][251][252] FBRs allow for changes in fluidizing flow rate which can affect the product selectivity between light gas and gasoline range components -as well as between olefin and paraffin production -within the gaseous fraction.…”
Section: Reactormentioning
confidence: 99%
See 2 more Smart Citations
“…[40] This configuration also allows for more facile recovery of spent catalysts for regeneration. [109] Fluidized-bed reactors (FBR) have better overall potential for scale-up than single-stage fixed-bed reactors because they can overcome operational problems such as heat transfer. [13,22,27,40,46,51,153,[250][251][252] FBRs allow for changes in fluidizing flow rate which can affect the product selectivity between light gas and gasoline range components -as well as between olefin and paraffin production -within the gaseous fraction.…”
Section: Reactormentioning
confidence: 99%
“…Because of this, expensive and operationally difficult feedstock preparation would be required for the utilization of fluidized bed reactors for industrial pyrolysis of plastic waste. [109] Conical spouted bed reactors (CSBR) have been staked as an appropriate alternative for the conversion of plastic, largely because they avoid operational issues that stem from bed defluidization as a result of melted plastics. [13,51,149,153,167,253] CSBRs allow for vigorous contact between different phases and have a lower chance of particle agglomeration in bed materials.…”
Section: Reactormentioning
confidence: 99%
See 1 more Smart Citation
“…They studied the use of zeolites in the catalytic pyrolysis of polyethylene (low density polyethylene (LDPE), high density polyethylene (HDPE)) waste, and established that the smaller the size of the zeolite and the higher the temperature, the higher the liquid fraction yield. Onwudili et al [19] worked with a mixture of plastics through catalytic pyrolysis, using catalysts such as FCC, ZSM-5 and zeolites Y. In this work, the yield of the liquid fraction decreased with the addition of the catalyst, and the liquid fraction had properties suitable for use as fuel, although the amount of aromatic compounds present increased.…”
Section: Introductionmentioning
confidence: 97%
“…Previously, Wu and Williams [11] indicated that gas yield and hydrogen production were improved by introducing steam to the catalytic pyrolysis of waste plastics mixture (HDPE, PP and PS). Regarding the effect of reaction temperature, higher pyrolysis temperatures can greatly influence product composition by increasing the gas product and decreasing the oil product [12,13]. Temperature has a crucial effect on waste plastic decomposition, as the yields of hydrogen and carbon nanotubes are affected by catalyst temperature [14].…”
Section: Introductionmentioning
confidence: 99%